2017
DOI: 10.1111/anae.14174
|View full text |Cite
|
Sign up to set email alerts
|

Recovery characteristics of patients receiving either sugammadex or neostigmine and glycopyrrolate for reversal of neuromuscular block: a randomised controlled trial

Abstract: Sugammadex more rapidly and reliably reverses rocuronium-induced neuromuscular block compared with neostigmine, but it is not known if subsequent patient outcomes, including nausea, vomiting and other aspects of recovery are modified. In this study, we compared the recovery characteristics of sugammadex and neostigmine/glycopyrrolate following reversal of neuromuscular block. This was a single-centre, randomised, blinded, parallel-group clinical trial in women undergoing elective day-surgical laparoscopic gyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
5
24
0
1
Order By: Relevance
“…A recent randomized controlled study compared sugammadex 2 mg/kg with a combination of neostigmine 0.4 mg/kg and glycopyrrolate 400 μg in laparoscopic gynecological surgery. There was no significant difference between both groups in the incidence of early PONV . Similar to another previous study, which was a comparison between a deep NMB group that was reversed with sugammadex and a shallow NMB group that was reversed with neostigmine, the number of patients who had PONV in both groups was similar .…”
Section: Discussionsupporting
confidence: 81%
“…A recent randomized controlled study compared sugammadex 2 mg/kg with a combination of neostigmine 0.4 mg/kg and glycopyrrolate 400 μg in laparoscopic gynecological surgery. There was no significant difference between both groups in the incidence of early PONV . Similar to another previous study, which was a comparison between a deep NMB group that was reversed with sugammadex and a shallow NMB group that was reversed with neostigmine, the number of patients who had PONV in both groups was similar .…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have compared sugammadex with conventional cholinesterase inhibitors in terms of the likelihood of PONV [12,[17][18][19][20]. Yagan et al reported that sugammadex was associated with a lower incidence of PONV within the first 1 h postoperatively compared to neostigmine, and less antiemetic agent use within the first 24 h postoperatively [12].…”
Section: Discussionmentioning
confidence: 99%
“…B. Rocuronium) durchzuführen. Dieses kann im Anschluss an die Behandlung schnell und nebenwirkungsarm mit Sugammadex antagonisiert werden[7,8].NarkoseführungDie Narkose sollte laut ESOPE-Protokoll als totale intravenöse Anästhesie (TIVA) aufrechterhalten werden[4]. Denn die Verwendung von Propofol und Opioiden in ▶ Tab.…”
unclassified